Обґрунтування вибору маркетингової стратегії молокопереробного підприємства - Шквиря, Наталя Олександрівна; Шквыря, Наталья Александровна; Shkvyria, Natalia (My University, 2019)
UK: У статті досліджено особливості практичного застосування методів стратегічного аналізу під час розроблення маркетингової стратегії молокопереробного підприємства. Визначено загрози та можливості зовнішнього середовища підприємства. Встановлено найбільш значущі чинники макро- та мікросередовища. За результатами стратегічного аналізу зовнішнього середовища запропоновано стратегічні альтернативи розвитку підприємства. У ході проведеного дослідження на основі методів стратегічного аналізу визначено маркетингову стратегію підприємства, адаптовану до ринку молока і молочних продуктів. Виявлено, що найбільш ефективною та перспективною є конкурентна маркетингова стратегія, яка спрямована на постійне зростання частки ринку підприємств та включатиме збільшення обсягів реалізації продукції за рахунок удосконалення комунікаційної політики, розвитку збутової мережі та розширення асортименту молочної продукції. RU: В статье исследованы особенности практического применения методов стратегического анализа при разработке маркетинговой стратегии молокоперерабатывающего предприятия. Определены угрозы и возможности внешней среды предприятия. Установлены наиболее значимые факторы макро- и микросреды. По результатам стратегического анализа внешней среды предложены стратегические альтернативы развития предприятия. В ходе проведенного исследования на основе методов стратегического анализа определена маркетинговая стратегия предприятия, адаптированная к рынку молока и молочных продуктов. Выявлено, что наиболее эффективной и перспективной является конкурентная маркетинговая стратегия, которая направлена на постоянный рост доли рынка предприятий и будет включать увеличение объемов реализации продукции за счет совершенствования коммуникационной политики, развития сбытовой сети и расширения ассортимента молочной продукции. EN: In the article the features of practical application of strategic analysis methods in the development of marketing strategy of dairy enterprise are investigated. The threats and opportunities of the enterprise environment are determined. The most significant factors of macro- and micro-environment are established. According to the results of strategic analysis of the environment, strategic alternatives to the development of the enterprise are proposed. The study of the macro-environment of the dairy enterprise suggests that there are more threats than opportunities, so companies in dairy producers need to implement research-based measures to overcome threats and effectively implement opportunities. As a result of the analysis of the micro-environment of the milk processing enterprise, the overriding features of the threats appeared, which indicates the prospect and high potential of functioning and development of the milk and dairy market in Ukraine. Using the SPACE matrix, it was determined that the strategic goals for the enterprise would be the most effective – the development of the distribution channels, the increase in the volume of dairy products sales due to the improvement of quality and the expansion of dairy products the range. As a result of the application of the Shell/DPM model, it was determined that PJSC “Combine “Pridneprovsky” takes the position “Strategy of strengthening competitive advantages” – the investigated enterprise has average competitive positions in the attractive industry. Possible strategic directions for the company are offered: expansion of product range, improvement of communication and marketing strategy. In the course of the research, based on the methods of strategic analysis, the marketing strategy of the enterprise was defined, adapted to the market of milk and dairy products. It is revealed that the most effective and promising is a competitive marketing strategy aimed at the continuous growth of the market share of enterprises and will include the following strategic activities – increase of sales volumes through improvement of communication policy, development of the distribution channels and expansion of dairy products the range.
The substance of the selection of the dairy enterprise the marketing strategy
Keywords: маркетинг; маркетингова стратегія; стратегічний аналіз; макросередовище підприємства; мікросередовище підприємства; молокопереробні підприємства; маркетинговая стратегия; стратегический анализ; макросреда предприятия; микросреда предприятия; молокоперерабатывающие предприятия; marketing; marketing strategy; strategic analysis; macroenvironment enterprise; microenvironment enterprise; dairy enterprise